(untitled) (Baghdad Science Journal, 2015)
The present study aimed to explain the dose-dependent possible deleterious effects of 30 day administration of Tramadol on some hematological and biochemical parameters of laboratory male rats (Rattus norvegicus), the study consisted of eighteen adult male rats randomly divided into three equal groups (each of six). Group 1 (control) were treated by intraperitoneal injection of normal saline solution (0.2 ml), group two (low dose) was treated by intraperitonealy (i.p) injection of Tramadol at a dose of 50 mg/kg/day, group three (high dose) was treated by intraperitonealy injection of Tramadol at a dose of 100 mg/kg/day for 30 days. At the end of experimental period, rats were sacrificed. Blood were collected by cardiac puncture to investigate blood film and biochemical parameters which include Aspartate transaminase (AST), Alanine transaminase (ALT), urea, and glucose. Results explained a significant reduction in hemoglobin (Hb), packed cell volume (PCV), and red blood cells count (RBC), in both treated group and significant elevation in WBC count which is clearly appeared in lymphocyte count, while the biochemical results showed a significant increased in ALT, blood urea, and decreased in blood glucose level in high dose treated group mostly